Effect of Flow Rate Variation on Solar Water Heater Performance - Baharudin Priwintoko; Agus Lutanto; Yusuf Subagyo; Saeful Romadhon; Agus Prasetyo (Akademi Inovasi Indonesia, 2025)
Solar energy potential in Indonesia is very large, yet its utilization for daily thermal needs still requires improvement through simple, economical, and efficient collector designs. This study analyzes the effect of fluid flow-rate variation on the performance of a trickle-type solar water heater with a V-shaped collector under local outdoor testing conditions. The novelty of the work lies in the combined evaluation of a V-shaped zinc-sheet absorber, trickle-type flow arrangement, north-facing 30° collector orientation, and practical flow-rate range of 2, 4, 6, and 8 L/min. The outdoor experiment was conducted from 09:00 to 12:00 Western Indonesia Time with repeated field observations for each flow-rate condition. Inlet temperature, outlet temperature, ambient temperature, collector temperature, cover temperature, wind speed, and solar radiation intensity were recorded and processed to determine useful heat gain, heat absorbed by the fluid, collector efficiency, fluid heat-absorption efficiency, and total efficiency. The results show that a lower flow rate produces a greater increase in fluid temperature, but it does not always produce the highest total efficiency. The 4 L/min flow rate provided the best performance, with a total efficiency of 55%, fluid heat-absorption efficiency of 71%, average fluid heat-transfer rate of 559.53 W, and estimated test-period fluid energy of 1678.59 Wh (6.04 MJ) during the 3 h test period. These findings indicate an optimum balance between fluid residence time and mass flow rate in improving solar water heater performance.